Focal Xanthogranulomatous Pyelonephritis in Brachydactyly Mental Retardation Syndrome (2q37 Deletion Syndrome) - Akyol Onder, Esra Nagehan; Ozkol, Mine; Nese, Nalan; Taneli, Can; Cankorur, Osman Orkun; Ozunan, Ipek (Journal of Pediatric Genetics, 2020)
Xanthogranulomatous pyelonephritis (XGP) is characterized by destruction of the renal parenchyma and granulomatous inflammation with lipid-laden foamy macrophages as well as inflammatory infiltration and intensive renal fibrosis. It generally occurs in adults, especially those in the fifth and sixth decades of life, but is occasionally seen in children as well. Brachydactyly mental retardation (BDMR) syndrome (OMIM 600430) is caused by a small deletion of chromosome 2q37 and is a rare condition, with roughly 100 cases reported worldwide. Here, we describe the case of a patient with deletion of chromosome 2q37, which is known as the BDMR syndrome, and XGP.
Keywords: brachydactyly mental retardation syndrome; 2q37 deletion syndrome; xanthogranulomatous pyelonephritis